2016
DOI: 10.1177/1358863x16644059
|View full text |Cite
|
Sign up to set email alerts
|

Differences in galectin-3, a biomarker of fibrosis, between participants with peripheral artery disease and participants with normal ankle–brachial index

Abstract: The aim of this study was to determine if Galectin-3 levels were different between participants with peripheral artery disease (PAD) and controls and to describe its relationship with markers of early atherosclerosis. Sixty participants recruited in two groups: a PAD group (n=31), ankle/brachial index (ABI) <0.90, and a normal ABI group (n=29), ABI 1-1.4. PAD participants were older (68.6 vs. 61.8 years, p=0.02), more commonly men (68% vs. 38%, p=0.02), with more cardiovascular risk factors (p<0.001). Galectin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 39 publications
(59 reference statements)
1
12
0
Order By: Relevance
“…Our findings are consistent with several proposed mechanisms of PAD progression, and confirm their importance in a relevant human study [ 29 , 30 , 31 ]. For example, TGFβ produced by vascular smooth muscle cells predicts fibrosis in the gastrocnemius of patients with PAD [ 30 ].…”
Section: Discussionsupporting
confidence: 92%
“…Our findings are consistent with several proposed mechanisms of PAD progression, and confirm their importance in a relevant human study [ 29 , 30 , 31 ]. For example, TGFβ produced by vascular smooth muscle cells predicts fibrosis in the gastrocnemius of patients with PAD [ 30 ].…”
Section: Discussionsupporting
confidence: 92%
“…Alterations in plasma galectin-3 concentrations in PAD have been investigated by two independent research groups. Casanegra et al [ 35 ] analyzed galectin-3 in 29 patients attending the Mayo Clinics with no evidence of PAD (normal ankle brachial index; ABI), and 31 patients with PAD (low ABI). They observed a mean galectin-3 concentration of 14.4 ng/mL in subjects with normal ABI, and approximately 22% increase in PAD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Patients exhibiting peripheral artery disease also demonstrated increased galectin-3 levels, and galectin-3 was positively associated with homeostatic model assessment, but not arterial elasticity and microalbuminuria following adjustment for age and sex ( 95 ). A prospective observational study indicated that elevated plasma galectin-3 levels were markedly associated with inflammation, severity and poor prognosis following intracerebral hemorrhage ( 96 ).…”
Section: Galectin-3 and Cardiovascular Diseasementioning
confidence: 99%